Neural Plasticity Lessons from Disorders of Consciousness - Demertzi, Athena; Schnakers, Caroline; Soddu, Andrea; Bruno, Marie-Aurélie; Gosseries, Olivia; Vanhaudenhuyse, Audrey; Laureys, Steven (Frontiers in Psychology, 2011)
Communication and intentional behavior are supported by the brain’s integrity at a structural and a functional level. When widespread loss of cerebral connectivity is brought about as a result of a severe brain injury, in many cases patients are not capable of conscious interactive behavior and are said to suffer from disorders of consciousness (e.g., coma, vegetative state /unresponsive wakefulness syndrome, minimally conscious states). This lesion paradigm has offered not only clinical insights, as how to improve diagnosis, prognosis and treatment, but also put forward scientific opportunities to study the brain’s plastic abilities. We here review interventional and observational studies performed in severely brain-injured patients with regards to recovery of consciousness. The study of the recovered conscious brain (spontaneous and/or after surgical or pharmacologic interventions), suggests a link between some specific brain areas and the capacity of the brain to sustain conscious experience, challenging at the same time the notion of fixed temporal boundaries in rehabilitative processes. Altered functional connectivity, cerebral structural reorganization as well as behavioral amelioration after invasive treatments will be discussed as the main indices for plasticity in these challenging patients. The study of patients with chronic disorders of consciousness may, thus, provide further insights not only at a clinical level (i.e., medical management and rehabilitation) but also from a scientific-theoretical perspective (i.e., the brain’s plastic abilities and the pursuit of the neural correlate of consciousness).